A Systematic Review of the Experiences and Support Needs of Informal Caregivers for People Who Have Attempted Suicide or Experienced Suicidal Ideation - George Lavers (International Journal of Environmental Research and Public Health, 2022)
Informal caregivers include family, friends, and significant others who provide important support for people who have attempted suicide or experienced suicidal ideation. Despite the prevalence of suicidal behaviour worldwide, they remain an understudied population. This review aimed to synthesise the literature on the experiences and support needs of informal caregivers of people who have attempted suicide or experienced suicidal ideation. We conducted a systematic review according to PRISMA guidelines. Searches of peer-reviewed literature in Medline, Emcare, Embase, EBM Reviews, and PsycINFO identified 21 studies (4 quantitative and 17 qualitative), published between 1986 and 2021. Informal carers commonly reported symptoms of depression and anxiety, for which they receive little assistance. They also expressed a desire for more involvement and education in the professional care of suicidality. Together, the studies indicated a need to improve the way informal caregiving is managed in professional healthcare settings. This review identified potential avenues for future research, as well as broad areas which require attention in seeking to improve the care of suicidal people and their caregivers.